Uncertainty in the response of sudden stratospheric warmings and stratosphere‐troposphere coupling to quadrupled CO2 concentrations in CMIP6 models - Ayarzagüena, B; Charlton-Perez, AJ; Butler, AH; Hitchcock, P; Simpson, IR; Polvani, LM; Butchart, N; Gerber, EP; Gray, L; Hassler, B; Lin, P; Lott, F; et al. (American Geophysical Union, 2020)
Major sudden stratospheric warmings (SSWs), vortex formation and final breakdown dates are key highlight points of the stratospheric polar vortex. These phenomena are relevant for stratosphere‐troposphere coupling, which explains the interest in understanding their future changes. However, up to now, there is not a clear consensus on which projected changes to the polar vortex are robust, particularly in the Northern Hemisphere, possibly due to short data record or relatively moderate CO2 forcing. The new simulations performed under the Coupled Model Intercomparison Project, Phase 6, together with the long daily data requirements of the DynVarMIP project in preindustrial and quadrupled CO2 (4xCO2) forcing simulations provide a new opportunity to revisit this topic by overcoming the limitations mentioned above.